Alcohol consumption in work-related occupationacl injuries - Kıran, Sibel; Konuk, Numan; Atik, Levent; Saltık, Banu; Şahin, Zühtü; Ayoğlu, Ferruh Niyazi (Journal of Dependence, 2006)
Objective: Occupational injuries are important in workplace because they require emergency health care and they have legal implications. There is not enough research done in our country about work-related injuries that occurred due to alcohol. Method: In this study 1845 occupational injury cases that were reported from emergency wards to the social security authority were evaluated retrospectively. Result: 7.2% of work-related-accident cases were found to have consumed alcohol prior to the accident at the emergency room admission. Discussion: It is necessary to explore and determine alcohol consumption and related problems with occupational injuries and records must be kept accordingly. Thus, helping future studies evaluating causality.